Pengaruh Model Flipped Classroom terhadap Peningkatan Hasil Belajar SBdP Siswa Kelas III SDN Pasekan 03 Ambarawa - Noviandani, Syela; Fakih, Moh; Sarwono, Ridha (Faculty of Teacher Training and Education of Undaris, 2023)
The background of this research is that the performance test assignments that are done at home will certainly be made by the students' parents and the lack of time at school to carry out performance test activities which results in low student learning outcomes in SBdP learning. The formulation of the problem is whether there is an effect of the flipped classroom model on increasing the learning outcomes of SBdP grade III students at SDN Pasekan 03 Ambarawa Even Semester 2022/2023 Academic Year. This study aims to describe the effect of the flipped classroom model on improving the learning outcomes of SBdP grade III students at SDN Pasekan 03 Ambarawa Even Semester 2022/2023 Academic Year. The design used in this research is Post test-Only Control Design. The research population was all third grade students at SDN Pasekan 03 Ambarawa. The sampling technique in this study was by using a random class sampling technique or Cluster Random Sampling with a sample of 34 students (17 students in the Experiment class and 17 students in the Control class). This research was conducted from January to February 2023 at SDN Pasekan 03 Ambarawa. The variables studied included: the Flipped Classroom learning model and SBdP learning outcomes. Data collection techniques in this study are tests and observations. Data analysis used inferential analysis techniques to describe the effect of SBdP learning outcomes in the form of student performance tests. The results showed that: the Flipped Classroom model had an effect on student learning outcomes. This can be seen by the differences in learning outcomes in the control class and the experimental class. Learning outcomes in classes that use the Flipped Classroom model increase compared to the control class.Keywords: Flipped Classroom Model, SBdP learning outcomes